PERSEPSI ANAK-ANAK TENTANG PERAN GENDER DALAM KELUARGA - Bangsawan, Indra (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2023)
This study explores how middle school children view gender roles in the family and how these views affect their interactions with other family members. Data were collected through in-depth interviews, observations, and documentation in several junior high schools in urban areas. The results of the study show that the traditional perception of the role of the father as the main breadwinner and the mother as the housekeeper is still very strong among children. However, there are also indications of a shift in views towards gender equality, especially in more modern family settings and in schools that promote gender equality. Mass media has also been found to have a great influence in shaping children's views on gender roles. These findings underscore the importance of education about gender equality from an early age and the role of parents, educators, and the media in shaping a more inclusive and equitable view of children. The implications of this study show the need for educational programs and social policies that support gender equality to create an environment conducive to children's development.